1978
DOI: 10.1016/0012-821x(78)90069-9
|View full text |Cite
|
Sign up to set email alerts
|

Early Cenozoic global plate reorganization

Abstract: Synthesis of regional plate movements reveals a major reorganization of global plate motion from Mesozoic to Cenozoic patterns that occurred primarily during the Eocene epoch (53.5 to 37.5 m.y.B.P.). The reorganization involved reorientation of relative plate motions with large N-S components into large E-W components, continuation of pre-existing E-W sea floor spreading, initiation of new E-W spreading, deceleration of spreading rates, and obduction of ophiolites. The reorganization is attributed to increase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(44 citation statements)
references
References 54 publications
1
41
0
Order By: Relevance
“…This pattern is suggestive of pulsations in hydrothermal activity that have been recorded elsewhere and have been related to tectonic reorganization events (Owen and Rea, 1985;Lyle et al, 1987). Reconstruction of the tectonic histories of many locations and examination of the sediment composition of these locations have revealed a clear link between active rifting events and periods of increased deposition of hydrothermal materials (some at oregrade levels) that preceded and/or accompanied these events (Rona and Richardson, 1978;Rona et al, 1983;Lyle et al, 1987;Olivarez and Owen, 1989). For example, Lyle et al (1987) examined the Neogene history of hydrothermal deposition in association with tectonic reorganizations along the East Pacific Rise by modeling the deposition of hydrothermal Mn in ridge flank sediments as a function of distance from the ridge axis.…”
Section: Sediment Composition and Rifting Mechanismsmentioning
confidence: 61%
“…This pattern is suggestive of pulsations in hydrothermal activity that have been recorded elsewhere and have been related to tectonic reorganization events (Owen and Rea, 1985;Lyle et al, 1987). Reconstruction of the tectonic histories of many locations and examination of the sediment composition of these locations have revealed a clear link between active rifting events and periods of increased deposition of hydrothermal materials (some at oregrade levels) that preceded and/or accompanied these events (Rona and Richardson, 1978;Rona et al, 1983;Lyle et al, 1987;Olivarez and Owen, 1989). For example, Lyle et al (1987) examined the Neogene history of hydrothermal deposition in association with tectonic reorganizations along the East Pacific Rise by modeling the deposition of hydrothermal Mn in ridge flank sediments as a function of distance from the ridge axis.…”
Section: Sediment Composition and Rifting Mechanismsmentioning
confidence: 61%
“…Marine geologists have known for 20 years or more that the earlier portion of the Eocene was a time of plate boundary rearrangement (Hayes and Pitman, 1970;Rona and Richardson, 1978). More recent work on the timing of plate boundary realignments in the Pacific Basin (Rea and Dixon, 1983;Caress et al, 1988) has shown the early Eocene to be an important time of change in patterns of spreading centers and transform faults.…”
Section: Tectonic Events and Sea-floor Hydrothermal Activitymentioning
confidence: 99%
“…In this paper (Fig.10), we attribute the timing to a ca. 45 Ma, mantle-wide rearrangement of convection (e.g., Courtillot et al, 2003), perhaps associated with the closing of the Tethys (Rona and Richardson, 1978;Patriat and Achache, 1984) or/and the sinking into the lower mantle of slabs that had accumulated near the 660 km transition zone (Fukao et al, 2001). The location of the BR may simply reflect a geochemically more fertile region of the upper mantle.…”
Section: What Produced Bermuda and The Bermuda Rise-why Then And Why mentioning
confidence: 99%
“…For example, Rona and Richardson (1978;see also Patriat and Achache, 1984) listed many Eocene events they attributed to the collision of India with Eurasia, i.e. the closing of the Tethys Ocean.…”
mentioning
confidence: 99%